Evaluation of Type and Frequency of Snacks Consumption in 3-6-Year-Old Children in Rabor and Baft Cities (2011) - Molouk Torabi; Hamid reza Poureslami; Allahyar Sajadi; Marzieh Karimi afshar; Mehrnaz Karimi afshar (Kerman University of Medical Sciences, 2015)
Introduction: Dental caries is a multifactorial disease. Diet has a major role in prevention of oral diseases as well as dental caries. The aim of the study was to evaluate the frequency and type of snack consumption among 3-6 year-old-children in Rbor and Baft in 2011. Method: This cross-sectional study was conducted on 240 kindergarten children aged 3-6 years old in Baft and Rabor cities through multiple stratified systematic sampling methods. Data were collected by a demographic questionnaire (sex, parents' education and their job, and number of children) and 2 checklists consist of daily type and frequency of snack consumption in kindergarten and at home. Data were analyzed in SPSS version 20 software using T and &chi2 tests. Results: In the present study, 125(52.1%) kids were boysand the rest were girls. 45.42% of snacks were cariogenic. The mean of weekly snack consumption by boys and girls were 45.68±18.98 and 46.05±18.10 respectively, and there were not any significant differences between them (P=0.879). The mean of snack consumption at home was meaningfully higher than that at kindergarten (P=0.000). Frequency of snack consumption in Rbor was higher than that in Baft, but the difference was not significant (P=0.493).There were not any meaningful statistical differences between fathers and mothers 'educational level and the mean of weekly snack consumption (P=0.643 and P=0.762). Conclusion: Based on the findings of the present study the mean of snack consumption at kindergartens in Baft and Rabor was high. However snacks provide a part of energy for children's growth, choosing healthy snack is necessary for dental health. Keywords: Snack Consumption, 3-6 Years, Children, Baft, Rabor Citation: Torabi M, PourEslami HR, Sajadi A, Karimi Afshar M, Karimi Afshar M. Evaluation of Type and Frequency of Snacks Consumption in 3-6-Year-Old Children in Rabor and Baft Cities(2011). Journal of Health Based Research 2015 1(2): 145-153.